PROFESIONALISME SEBAGAI PEMODERASI PENGARUH INDEPENDENSI PADA KINERJA AUDITOR - Novia Made, Tirza; Aryanto, Dodik (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
The quality of the financial reports are focused on the performance of the auditors. To achieve a good performance, an auditor must have an attitude of independence in themselves. However, the fact shows that the auditor independence is now declining, so tha it also needs to be supported by the attitude of professionalism in carrying their duties. The inconsistency of the results before, so this study aims to determine the effect on the performance of the auditor's independence and also aims to determine whether professionalism will moderate the influence of independence on the auditor’s performance. The study was conducted in KAP that listed on the IAPI area of ??Bali in 2015. The samples were selected using a saturated techniques. The data was obtained through the deployment of a questionnaire to the auditors and the analytical techniques that is used in this research is simple regression analysis and MRA with an absolute difference test. The results showed that the test instruments and classical assumptions are met. Based on the analysis, it is known that the independence give a positive and significant impact on the performance of the auditors of Registered Public Accounting Firm in Bali. The study also found that professionalism is unable to moderate the influence of independence on the auditor’s performance.
Keywords: independence, professionalism, performance of auditor